An Evaluation Readiness to be Semi-Autonomous Hospital of Luang Prabang Provincial Hospital of Luang Prabang Provincial Hospital: https://doi.org/10.69692/SUJMRD100420 - Latisawath, Anousack; Yangsansay, Chahue; Vatthana, Mongkhoun (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
The purpose of the research is: 1) To evaluate the readiness of being semi-autonomous hospital of Luang Prabang Provincial Hospital. 2) To study the comparative analysis of the evaluation readiness of the semi-autonomous hospital of Luang Prabang Provincial Hospital. The sample group in the study was the director and medical staff of the Luang Prabang Provincial Hospital. In the actual data collection, a total of 70 people were returned, and the statistical program was used to analyze the data. Standard deviation and inferential statistics (independent-simples T-test and one-way ANOVA) hypothesis testing. The study found that the majority of respondents were female, aged 31–40, married, bachelor's degree holders, with 16 years of work experience, and had never attended a semi-autonomous hospital transformation meeting. The research results found that: the evaluation readiness to be Semi-Autonomous hospital of Luang Prabang Provincial Hospital as a whole has a level of readiness at a very high level = 3.88, SD = 0.89 which is the average value rating from large to small financial self-support has a level of readiness at a very high level = 3.99, SD = 0.95; followed by operational self-reliance with a high degree of readiness = 3.95, SD = 0.89; Administrative management self-esteem has a high readiness level = 3.84, SD = 1.01 and personal self-confidence has a high readiness level = 3.76, SD = 0.97. The results of the comparison by distinguishing by individual factors found that age, work experience, and participation in training in semi-autonomous hospitals have differences in evaluating readiness to transform Luang Prabang Hospital into a semi-autonomous hospital with statistical significance. 0.05. For other individual factors, there is no difference.